Menschenrechte im Unternehmen durchsetzen - Hamm, Brigitte (Forschung aus der Hans-Böckler-Stiftung, 2017)
International labor rights continue to gain in importance as globalization progresses. Based on case studies and expert interviews, the authors discuss the UN Guiding Principles on Business and Human Rights. In doing so, they identify points of contact for trade unions and works councils and point out strategies, opportunities for participation and instruments for safeguarding workers' rights in companies worldwide.